Eating Habits and School Performance in Students of Primary Education - Prieto Andreu, Joel Manuel (Journal of Modern Educational Research, 2024)
Background: Maintaining a proper diet is crucial, particularly for children undergoing the critical phases of growth and development. Objective: This study aims to investigate the association between eating habits and academic performance among students in Primary Education. Methods: The research adopts a descriptive-correlational approach with a cross-sectional design, utilizing a sample comprising 427 students (242 boys and 185 girls) in the sixth year of Primary Education. The instrument used is a self-developed ad hoc questionnaire, encompassing dietary habits, food choices at school and home throughout a typical week (including breakfast, lunch, snack, and dinner), and academic performance assessed by the student’s tutor. Results: Significant associations were observed between academic performance and the consumption of pasta, fruit, and meat (P=0.00), as well as pastries and fish (P<0.05). Students with a preference for these foods tend to exhibit higher academic performance. However, no significant correlations were identified for “vegetables”, and there were no discernible associations between food groups and academic performance based on gender or body mass index (BMI). Conclusion: Individuals displaying proper eating habits, such as consuming five daily meals, avoiding food wastage, and incorporating pasta, fruit, and meat into their diet, demonstrate commendable academic performance.
Keywords: academic performance; nutrition; feeding behavior; child